Assessment of College Students’ Preference on the Usage of Google Drive as a Learning Platform: An Empirical Evidence - Abubakar, Mahmud Tukur (American International Journal of Social Science Research, 2019)
This research assessed College Students preference on the Usage of Google Drive as a learning platform in north-east Nigeria. The study had three objectives, three research questions and three null hypotheses. Descriptive survey research design was used for the study. The population of the study was 263 three hundred level business education students in north-eastern Nigeria. Four rating scale structured questionnaire titled “College students’ preference of Google Drive (CGD”) was used for data collection. The instrument was validated by experts from the Faculty of Technology Education, Abubakar Tafawa Balewa University Bauchi. The researcher personally administered the instrument assisted by 3 research assistants. Data collected was analyzed using Mean and standard deviation statistical tools to answer the research questions. The result of the study reveals that students used Google Drive for assignments, study and downloading of materials. Based on the outcome of the study, it was concluded that Google Drive platform provide undergraduate business education students with opportunities to enhance and assess current educational information. It was recommended that lecturers and all stakeholders who handle business education courses should be encourage to adopt the use of Google Drive as a learning platform, The business education students should utilize and exploit maximally the opportunities provided by the use of Google Drive as a learning platform for learning activities with the help of their lecturers etc. in addition useful suggestions for further research are equally made.